Ø§Ù„ÙÙƒØ±Ø© Ø¹Ù† Ø¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„ØªØ±Ø¨ÙˆÙŠ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø«Ø§Ù†ÙŠØ© - Hasanuddin Tosimpak (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2022)
The Planning of language teaching has to be planned as good as possible to reach the purpose of that teaching. The Planning is not only about the theories but more than that it is about the other matters such as policy, organizing, these matters have role to help the teacher to succeed the program of foreign language teaching and how to implement an environment that can support the successful of language teaching and the capability of teacher about knowledge that will be taught. The concept of Educational Linguistics can describe about how a process or a plot of language teaching is arranged, the successful of language teaching is not only about language theories its self but also about the organizing and language teaching policy. This research is a library research which is included in the type of qualitative research, the data are collected from some resources that are devide into two parts, primary and secondary. The Primary resource is the book about educational linguistics written by Jos Daniel Parera and the book edited by Bernard Spolsky and Francis M. Hult with the title â€œThe Hand Book Of Educational Linguisticsâ€. The Secondary is the books about linguistics in general and the books about teaching and language teaching.